Failure of the Noncontact Bridging Periprosthetic Plating System: A Single-Institution Experience - Michael R. Mercier, MD, MSc; James M. Broderick, MBBS, MCh; Catherine S. Hibberd, MBBS, MS; Shane P. Russell, MB, BCh, BAO, MCh, MRCSI; Mansur M. Halai, MBChB; Amit Atrey, MD, MSc, MRCS; Aaron Nauth, MD, MSc; Amir Khoshbin, MD, MSc (Arthroplasty Today, 2025)
Background: Periprosthetic femur fractures (PFFs) are challenging complications following total joint arthroplasty. Locking compression plates have emerged as a preferred option because of their stability and ability to be placed in a minimally invasive fashion. Surgical techniques for their application have been well-described; however, there are limited reports of failure. Here, we present 6 unique cases of implant failure using the Noncontact Bridging (NCB) Periprosthetic Plating System in the management of PFF. Methods: A retrospective chart review was conducted of all open reduction internal fixation procedures using the NCB plating system for PFF performed at a single tertiary academic trauma center from 2015 to 2022. Instances of postoperative implant failure were selected for review. Surgical information regarding their index PPF and subsequent open reduction internal fixations were collected. Results: Of the 44 instances the NCB plating system was used, 6 (13.6%) cases of implant failure were identified. Four out of 6 cases occurred within 4 months of fixation. Five of the failures were due to plate fracture and 1 by plastic deformation. Failure of the plate was noted at the tip of the prosthesis in 5 out of 6 cases. Stress concentration was minimized by avoiding the use of 3 consecutive screw plate holes in all cases. Conclusions: Here we present the largest case series to date of NCB plating system failure. These cases highlight the need for further surveillance of plate failure in the management of PFF, as well as ways in which system design could be improved. Level of Evidence: IV.